MPPT Menggunakan Metode Hibrid JST dan Algoritma Genetika Untuk Sistem Photovoltaic - Gunawan Wibisono; Sholeh Hadi Pramono; Muhammad Aziz Muslim (Jurnal EECCIS, 2014)
Maximum Power Point Tracking is a method to track power point of an energy source in order to generate maximum power. One of the MPPT method for photovoltaic system is fractional open voltage MPPT. In this paper the fractional open voltage MPPT is modified by using artificial neural network trained using genetic algorithm. Artificial neural networks are successfully trained by using genetic algorithm. The best mean squared error (MSE) value obtained is 0.000453. The network tested using test data, yielding average error = 0.00949509 and MSE = 0.00012814. The neural network-based MPPT can improve the fractional open voltage MPPT by 4.79%.Index Terms---Genetic Algorithm, MPPT, Neural Network, Photovoltaic